Designing a Model for Competitiveness Measurement of Selected Tourism Destinations of Iran (The Model and Rankings). Issue 4 (4th July 2019) - Boroomand, Babak; Kazemi, Ali; Ranjbarian, Bahram
ABSTRACT: Destination competitiveness is the ability to sustain or improve market position and market share of a destination over a period of time. Different markets have different expectations which increase the importance of features a destination should provide in order to achieve competitive advantage. The results of this study show that the domestic model of Iran's destinations competitiveness comprises 9 major indices. These indices are made of 64 variables which have been derived from literature reviews and qualitative surveys. The results of running the model for all selected destinations are consistent with the destinations' tourist statistics except for one destination (Qom).